ACTIVITY OF ANTIOXIDANT SYSTEM ENZYMES IN MUSCULAR TISSUE OF RATS WITH MUSCLE PHLEGMON - Popova, L.D.; Sherban, N.G.; Васильєва, І.М. (World of Medicine and Biology, 2010)
Superoxide dismutase, catalase activities, ascorbic acid level in blood and muscles of rats with muscle phlegmon were studied. The increase of superoxide dismutase activity in blood, normal and damage regions of muscle; the increase of catalase activity in blood and damaged region of muscle; the decrease of catalase activity in normal region of muscle as compared with control were found. Ascorbic acid redistribution between normal and damaged region of muscle with phlegmon was found.
Keywords: rats; phlegmon; superoxide dismutase; catalase; ascorbic acid